Mexican cactus diversity: environmental correlates and conservation priorities - Godinez Alvarez, H.=700 1 Ortega Baes, P.
(En, Es)
ilus., 65 ref.
Keywords: CACTACEAE; BIODIVERSIDAD; COMPOSICION BOTANICA; ESPECIES EN PELIGRO DE EXTINCION; MEXICO